2012
DOI: 10.1590/s2179-64912012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal auditory processing in rural workers exposed to pesticide

Abstract: Workers exposed to pesticide performed bellow average on Temporal Auditory Processing tests. There was association between the index of exposure to pesticides and worse performance in Temporal Auditory Processing tests, suggesting that the pesticides may be harmful to central auditory pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
2
7
0
4
Order By: Relevance
“…Estes dados podem estar relacionados a um movimento de invisibilidade na percepção dos riscos, uma estratégia defensiva de negação dos impactos à saúde, mesmo cientes dos prejuízos que essas substâncias poderiam ocasionar 27 De maneira geral, a banalização da contaminação pode estar associada ao uso indiscriminado de agrotóxicos em diversas situações: no dia a dia dos lares, nas maciças campanhas de combate aos mosquitos, nas desinsetizações rotineiras, na comercialização clandestina desses produtos ou na falta de assistência técnica ao produtor, mas, apesar do reconhecimento dos seus efeitos deletérios à saúde e ao ambiente, muitos agricultores ainda veem no uso de agrotóxicos a possibilidade concreta de uma maior produção de alimentos 2 . Ainda que esta produção alimentícia não atenda às condições adequadas de saúde do trabalhador 28 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estes dados podem estar relacionados a um movimento de invisibilidade na percepção dos riscos, uma estratégia defensiva de negação dos impactos à saúde, mesmo cientes dos prejuízos que essas substâncias poderiam ocasionar 27 De maneira geral, a banalização da contaminação pode estar associada ao uso indiscriminado de agrotóxicos em diversas situações: no dia a dia dos lares, nas maciças campanhas de combate aos mosquitos, nas desinsetizações rotineiras, na comercialização clandestina desses produtos ou na falta de assistência técnica ao produtor, mas, apesar do reconhecimento dos seus efeitos deletérios à saúde e ao ambiente, muitos agricultores ainda veem no uso de agrotóxicos a possibilidade concreta de uma maior produção de alimentos 2 . Ainda que esta produção alimentícia não atenda às condições adequadas de saúde do trabalhador 28 .…”
Section: Discussionunclassified
“…Estudos revelaram os benefícios do uso da AAF no diagnóstico da perda auditiva associada a agentes físicos e químicos [30][31][32][33][34][35][36][37] e pesquisas sinalizam para a possibilidade do efeito ototóxico dos agrotóxicos 6,23,28,29,31,[37][38][39][40][41] , entretanto nenhum trabalho relacionando, exclusivamente, a exposição aos agrotóxicos e a realização de AAF foi encontrado.…”
Section: Discussionunclassified
“…Normal hearing thresholds is not enough evidence to assert that there is auditory comprehension. It is necessary to analyze and interpret the audio signal in order for it to become a message with meaning (3) . Auditory skills evaluated through behavioral tests include: detection, audio source localization, auditory discrimination, selective attention, auditory figure-ground, auditory closure, binaural separation and integration and auditory sequential memory, considering that CAP evaluation classifies the individual as normal or altered (4) .…”
Section: Introductionmentioning
confidence: 99%
“…The occupational hearing loss has been mostly only attributed to noise although there are other agents that might contribute to its potentiation, among them pesticides [2][3][4][5][6][7][8][9][10] . Studies have linked exposure to otoagressives agents, noise and ototoxics, at higher frequencies above 8kHz, before the others [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported harmful effects of pesticides to peripheral and central auditory pathways and in which the organophosphates can also be responsible for neurotoxicity to the auditory system 2,3,5,6,7,10 .…”
Section: Introductionmentioning
confidence: 99%